IMPLEMENTATION AND ANALYSIS OF THE INTERNET OF THINGS SYSTEM FOR ELECTRICAL ENERGY MONITORING AT INSTITUT TEKNOLOGI TELKOM PURWOKERTO - Agung Enriko I Ketut; Mas Aly Afandi; Herryawan Pujiharsono; Fikri Nizar Gustiyana; Hedi Krishna; Filbert H. Juwono (Informatika, Universitas Jenderal Soedirman, 2023)
Measurement of electric power usage is carried out using simple measuring instruments and the recording is still manual so that the data obtained is not real-time and accurate. This research aims to implement an electrical energy monitoring system using the Internet of Things (IoT) to obtain real-time information related to electrical energy in the education industry. This research uses an Industrial Grade Power Meter to get a more accurate measurement value. To connect the Power Meter device with the IoT system, this research uses Modbus RS485 communication and a mini PC to process data from the meter, so that the data can be sent to a server using the MQTT communication protocol, and displayed on the Dashboard. The test results of this study indicate that the monitoring system can be implemented and the system runs well with end-to-end measurement results. From the measurement results, the current value (3 phase average) has an average deviation of 0.001 Amperes, Voltage (3 phase average) has an average deviation of 0.519 V, Power factor has an average deviation of 0.012, Active power has a deviation average of 0.000 kW, reactive power with an average deviation of 0.000 kVAR, apparent power with an average deviation of 0.000 kVA and frequency with an average deviation of 0.124 Hz. Then the MQTT protocol has a quality of service with index 4 based on TIPHON standardization on delay, throughput, and packet loss parameters, and index 3 based on TIPHON standardization on jitter parameters.